Insight in ultrasonic shear reflection parameters by studying temperature and limonene influence on cocoa butter crystallization. (February 2016) - Rigolle, Annelien; Foubert, Imogen; Hettler, Jan; Verboven, Erik; Martens, Arvid; Demuynck, Ruth; Van Den Abeele, Koen
Abstract: In this study an inverse model was developed to derive relevant ultrasonic parameters from ultrasonic shear reflectometry measurements. The inverse model includes four variable parameters: t ind (induction time), K (crystallization rate), v s2 (shear ultrasonic velocity) and a s2 (shear ultrasonic attenuation coefficient). Both the temperature effect and the effect of a minor component limonene (in different concentrations) on the isothermal crystallization of cocoa butter were studied with the ultrasonic shear reflectometry technique and associated inverse model. Subsequently, the ultrasonic parameters were compared with results of conventional techniques to monitor fat crystallization (DSC, PLM). The study shows that t ind and K provide information on the kinetics of the microstructure development. The parameter v s2 is related with the equilibrium SFC, while a s2 is both influenced by the SFC and the organization of the crystals in the network, yielding information about the microstructure of the crystallized samples. Industrial relevance: The microstructure of crystallized fat determines to a large extent the macroscopic properties of fat rich products, such as texture, mouthfeel, … Hence, monitoring the crystallization behavior (including not only the primary crystallization but also the microstructural development) during the production process is of utmost importance in order to obtain high quality end products. The ultrasonic shear reflectometry technique is a fast non-destructive technique which provides quantitative data about the crystallization process based on an inverse model. The simplicity of the technique offers potential for inline control. This may be beneficial to evaluate the crystallization process under different process conditions and to stimulate product innovation as more insight can be obtained in the microstructure development of new products. Highlights: Shear ultrasonic reflection technique measures microstructure development of fats. Quantitative parameters can be obtained by an inverse model. Parameters tind and K indicate the kinetics of microstructure development. Shear velocity (vs2 ) and shear attenuation (as2 ) indicate SFC and microstructure.